Desenvolvimento de um reator eletrônico de baixo custo para iluminação a LED - Lima, Fabio Pereira de (2015)
The exploitation of resources is increasing along with the growth of populations. This has motivated human beings to seek ways to minimize the impact of resource consumption, electricity is one of those. Artificial lighting for example, now accounts for about 20% of all energy consumption in the world. The lamp that started the mark of using light sources, the incandescent has low efficiency and gradually is being banished, so it is necessary to study its replacement by more efficient sources. Initially, fluorescent lamps were the first that gained acceptance in the market, but these have the elemental mercury in its composition, which should also be banned because it is a major contaminant. It is estimated that only 6% of the nearly 300 million fluorescent lamp produced in Brazil per year are recycled. As a result, the LED, specifically the power LEDs, have become attractive because, besides not being pollutants, promote a very significant savings over the others, both in power consumption, as in its acquisition, because they have an average life of about 50,000 hours (five times that of fluorescent lamps and fifty times that of incandescent bulbs). The peculiarity of LEDs is that these are fed with low voltage and direct current and must monitor its temperature and current, which can damage it and reduce its useful life. On that front, this study sought to do a literature review on the operation and characteristics of the LEDs and the implementation and research of the use of converters (basic topologies) for the development of a low cost ballast to suggest the replacement over other types of lamps. With these, the Buck converter topology would meet this demand satisfactorily through current sensor feedback.